The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/piq.20002
|View full text |Cite
|
Sign up to set email alerts
|

Crisis planning: Survey results from Hurricane Katrina and implications for performance improvement professionals

Abstract: Modern organizations constantly face unparalleled changes and uncertainty in the competitive world, thus requiring strategic planning to mitigate crisis conditions. Underscoring crisis plans are performance interventions that prepare employees, technological systems, and the organizational culture to effectively respond to a crisis event. However, crisis planning has been an overlooked area in the performance improvement literature. In the present study, we review results of a survey on crisis planning conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The role of crisis management teams in crisis planning were also identified by 56% of the respondents in a separate survey on crisis management preparation (American Management Association, 2005). The results of these surveys and our content review of numerous empirical and conceptual studies (see Hutchins, Annulis & Gaudet, 2008, for a full review) reveal that crisis communication, crisis management teams, training, and BCPs are critical components in crisis planning. Although these components are discussed in other articles included in this issue, a brief overview of each component is provided here to build an initial understanding.…”
Section: Crisis Management Modelmentioning
confidence: 98%
“…The role of crisis management teams in crisis planning were also identified by 56% of the respondents in a separate survey on crisis management preparation (American Management Association, 2005). The results of these surveys and our content review of numerous empirical and conceptual studies (see Hutchins, Annulis & Gaudet, 2008, for a full review) reveal that crisis communication, crisis management teams, training, and BCPs are critical components in crisis planning. Although these components are discussed in other articles included in this issue, a brief overview of each component is provided here to build an initial understanding.…”
Section: Crisis Management Modelmentioning
confidence: 98%
“…Research on the role of professionals (Hutchins et al, 2008) during the Hurricane Katrina disaster in 2005 showed the necessity of role change in water management. The Katrina storm surge caused most (2/3) breaches in human designed levees, flooding 'safely', water-managed residential areas (ASCE, 2007).…”
Section: )mentioning
confidence: 99%
“…In any case, if any crises should occur again, then the NOC should supervise that they are han dled appropriately. Hutchins et al (2008) state that this phase requires the NOC to engage in critical reflection on the crisis experience. The NOC should analyse the crisis impact on central and ancillary system processes, and then adapt behaviours and systems to improve crisis management practices.…”
Section: Recommendation: Actions To Limit the Impact Of A Crisismentioning
confidence: 99%